Epibionts Reflect Spatial and Foraging Ecology of Gulf of Mexico Loggerhead Turtles (Caretta caretta) - Silver-Gorges, Ian; Ingels, Jeroen; dos Santos, Giovanni A. P.; Valdes, Yirina; Pontes, Leticia P.; Silva, Alexsandra C.; Neres, Patricia F.; Shantharam, Arvind; Perry, Destin; Richterkessing, Andrew; Sanchez-Zarate, Sofia; Acevedo, Laura; et al. (Frontiers in Ecology and Evolution, 2021)
Sea turtles are exposed to numerous threats during migrations to their foraging grounds and at those locations. Therefore, information on sea turtle foraging and spatial ecology can guide conservation initiatives, yet it is difficult to directly observe migrating or foraging turtles. To gain insights into the foraging and spatial ecology of turtles, studies have increasingly analyzed epibionts of nesting turtles, as epibionts must overlap spatially and ecologically with their hosts to colonize successfully. Epibiont analysis may be integrated with stable isotope information to identify taxa that can serve as indicators of sea turtle foraging and spatial ecology, but few studies have pursued this. To determine if epibionts can serve as indicators of foraging and spatial ecology of loggerhead turtles nesting in the northern Gulf of Mexico we combined turtle stable isotope and taxonomic epibiont analysis. We sampled 22 individual turtles and identified over 120,000 epibiont individuals, belonging to 34 macrofauna taxa (>1 mm) and 22 meiofauna taxa (63 µm - 1 mm), including 111 nematode genera. We quantified epidermis 13C and 15N, and used these to assign loggerhead turtles to broad foraging regions. The abundance and presence of macrofauna and nematodes did not differ between inferred foraging regions, but the presence of select meiofauna taxa differentiated between three inferred foraging regions. Further, dissimilarities in macrofauna, meiofauna, and nematode assemblages corresponded to dissimilarities in individual stable isotope values within inferred foraging regions. This suggests that certain epibiont taxa may be indicative of foraging regions used by loggerhead turtles in the Gulf of Mexico, and of individual turtle foraging and habitat use specialization within foraging regions. Continued sampling of epibionts at nesting beaches and foraging grounds in the Gulf of Mexico and globally, coupled with satellite telemetry and/or dietary studies, can expand upon our findings to develop epibionts as efficient indicators of sea turtle foraging and spatial ecology.